IC 9417 Analysis Of Metal/Nonmetal Underground Mining Accidents Involving Mobile Mining Equipment - P. A. Hendricks (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This U.S. Bureau of Mines (USBM) report identifies and evaluates factors responsible for metal/nonmetal (M/NM) underground mining accidents involving mobile equipment. Information regarding the occurrence and severity of the accidents, the type of equipment involved, the primary and contributing causes, and preventive measures is included. The goal of this report is to provide information that will aid mine operators and safety managers in the recognition of hazards associated with operating mobile mining equipment in an underground mining environment.